Impact of pharyngeal endoscopic tip placement and water flushing interval on upper respiratory tract disorders in horses undergoing overground endoscopy. (6th August 2018) - M Givney, C. L.; Sweeney, J.; Gough, K. F.; Hill, E. W.; Katz, L. M.
Summary: Background: Endoscopic tip placement in the pharynx and water flushing interval (FI) may affect exercising upper respiratory tract (URT) endoscopic results. Objectives: To determine associations between the endoscopic tip position in the pharynx and automated FI with overground endoscopic (OGE) results. Study design: Randomised balanced 2X5 factorial design. Methods: A total of n = 200 horses undergoing OGE were randomly assigned into 10 groups (n = 20/group) of different automated endoscopic FIs (no flushing, 60, 120, 180, 240 s) with the endoscope tip positioned either rostrally (position A) or caudally (position B) in the pharynx. Endoscopic videos were analysed and all URT abnormalities graded using published scales. Disorders with ≤10% prevalence were excluded from the final analysis with only arytenoid asymmetry at exercise (AAex), vocal fold collapse (VFC), palatal dysfunction (PD) and medial deviation of the aryepiglottic folds (MDAF) included. The association of endoscope position and FI with URT disorders was assessed using ordinal regression models with P≤0.05 significant. Results: Endoscope tip positioning was significantly associated with PD grading (P = 0.002), with 63/100 horses diagnosed with PD in position A and 45/100 in position B. No other significant direct associations between URT disease and endoscope tip position were identified, although interactions between exercise velocity and endoscope position affected MDAF grade. FI was not directly associated with alterations in disorder grading, although interactions between exercise velocity and FI appeared to affect MDAF grade. Main limitations: The same horse was not evaluated under each test condition potentially resulting in sample bias. Interactions between disorders were not evaluated. The sample size was insufficient to conclusively explore relationships between all factors and disorder grading. Conclusions: Position of the endoscope tip within the pharynx appears to affect grading of PD during OGE examination. Exercise velocity may affect MDAF grade through interactions with endoscope position and FI.